Stabilization Splint Therapy for Patients with Temporomandibular Disorders Improves Opening Movements and Jaw Limitation and Attenuates Pain by Influencing the Levels of IL-7, IL-8, and IL-13 in the Gingival Crevicular Fluid - Renata Sikora; Kristina Duspara; Anita Matić; Ana Petrović; Kristina Kralik; Robert Smolić; Miroslav Sikora; Martina Čalušić Šarac; Kristina Bojanić; Martina Smolić (Medicina)
Background and Objectives: In recent years, numerous studies have investigated and analyzed the levels of molecular biomarkers of temporomandibular disorders (TMD) from various tissue samples and body fluids. However, no study has investigated gingival crevicular fluid (GCF) in TMD patients. The purpose of this study was to determine the concentrations of pro-inflammatory cytokines in GCF before and after stabilization splint (SS) therapy in patients with painful TMD, to investigate whether SS administration causes changes in the concentrations of pro-inflammatory cytokines. An additional aim was to investigate the relationship of GCF cytokine levels with chronic pain intensity and clinical parameters. Materials and Methods: This prospective cohort study included 36 patients who were diagnosed with painful TMD using the Diagnostic Criteria for TMD (DC/TMD). GCF samples were collected at baseline before SS treatment (T0) and at one month (T1) and three months (T2) after the start of therapy. Customized ProcartaPlex Multiplex assays from eBioscience (Invitrogen™, Thermo Fisher Scientific, Viena, Austria) were used for the quantitative analysis of pro-inflammatory cytokines (IL-1β, IL-6, IL-7, IL-8, IL-13, and TNF-α). Patients filled out Croatian versions of questionnaires for self-assessment from Axis II DK/TMP: Graded Chronic Pain Scale (v2) (GCPSv2) and Jaw Function Limitation Scale-20 (JFLS-20). Results: The results showed that the GCF levels of IL-7 (Friedman’s test, p = 0.008) and IL-13 (Friedman’s test, p = 0.003) were significantly decreased at T2. The GCF level of IL-13 was in negative correlation with chronic pain grade score at T2 (Rho = −0.333), while the GCF level of IL-8 was in positive correlation with mobility limitation (Rho = 0.382) at T1. Conclusions: The results indicate that SS therapy might have a role in reducing inflammation and that the GCF could be a valuable medium for assessing molecular biomarkers.